2018
DOI: 10.1111/ijcp.13235
|View full text |Cite
|
Sign up to set email alerts
|

Second cancers in Hodgkin's lymphoma long-term survivals: A 60-year single institutional experience with real-life cohort of 871 patients

Abstract: Patients with HL are generally at great risk of developing SC, which is significantly increased especially by the use of radiotherapy. We suggested special follow-up schema for patients after initial HL treatment suitable for daily real-world clinical practice. The system depends on gender, form of HL treatment and especially the form of radiation therapy in terms of location of radiation fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In 771 FL patients from the pre-rituximab era, the risk ratio (RR) for leukaemia was 10Á4 (95% Cl: 4Á5-20Á5) (Mudie et al, 2006). In 871 Hodgkin lymphoma (HL) patients with a median follow-up of 12 years, the SIR was 5Á8 (95% Cl: 2Á3-12Á0) for secondary leukaemia (Petrakova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In 771 FL patients from the pre-rituximab era, the risk ratio (RR) for leukaemia was 10Á4 (95% Cl: 4Á5-20Á5) (Mudie et al, 2006). In 871 Hodgkin lymphoma (HL) patients with a median follow-up of 12 years, the SIR was 5Á8 (95% Cl: 2Á3-12Á0) for secondary leukaemia (Petrakova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the follow-up of patients after treatment for Hodgkin's lymphoma 8 , in a single center, the risk of developing the second cancer was 80.8%. Breast cancer was the second most frequent, second only to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity modulated proton therapy (IMPT) in DIBH may have an additional benefit [30]. A recent and large analysis of the rate of second cancers in Hodgkin survivors treated at a median age of 34 years revealed that the most common second cancer is lung cancer in 17.5% of all patients with a general standardized incidence ratio of 2.9 [31]. In order to mitigate the risk for secondary malignancy in the lungs the dose distribution for our patients was anterior-posterior weighted and the reduced lung dose by DIBH may also contribute to lower this risk.…”
Section: Discussionmentioning
confidence: 99%